Implementation of continuous-grouped-self-learning (CGSL) system in engineering education - Mohd Azau, Mohd Azrin; Abas, Ahmad Fauzi; Saripan, M. Iqbal; Wan Adnan, Wan Azizun; Noordin, Nor Kamariah; Ismail, Alyani; Mokhtar, Makhfudzah; Samsudin, Khairulmizam; Mashohor, Syamsiah; A. Rasid, Mohd Fadlee; Raja Abdullah, Raja Syamsul Azmir; Ahmad, Faisul Arif (Canadian Center of Science and Education, 2008)
This paper presents a new method in engineering education called a continuous-grouped-self-learning (CGSL) system. In general, based on feedbacks acquired from the student at the end of the implementation, students better understanding and appreciation to the courses been taught. Out of 60 students 71.7% admitted that this learning system has improved their study style and knowledge acquisition, which then agreed to be implemented in future. The observation shows that this system increases the appreciation to the knowledge better than conventional method. Apart from that the system also produced better students in term of responsibility, self-confidence, competitiveness, group work, and knowledge sharing. This is realized with the implementation of mock teaching assessment.